Pelatihan Manajemen UMKM Dengan Pemanfaatan LimbahTempurung Kelapa Menjadi Bahan Bakar Briket di DesaBatanggadis - Ali Yusron (Yayasan Perguruan Kampus, 2025)
Indonesia is one of the tropical countries that has abundant coconut plants. Coconut plants have manybenefits ranging from roots, trees to fruits. Currently, coconut trees have been widely utilized but notoptimally, especially coconut solid waste. Coconut solid waste can be converted into briquettes that canbe further utilized as environmentally friendly alternative fuels. Briquettes are blocks of material thatcan be used as fuel to start and maintain a fire. Batanggadis Village, West Panyabungan District,Mandailing Natal Regency, North Sumatra Province is one of the villages where most of the peoplecook with firewood. Firewood is a cheap and easily obtained fuel compared to LPG gas. In addition,Batanggadis Village is known as one of the areas producing coconut shells, but it is not utilizedoptimally. Therefore, it is necessary to increase understanding and awareness in processing coconut shellsinto briquettes through training for the community in order to increase the added value of waste andincrease community income. And with UMKM management training, human resources in Batanggadisvillage are increasing.